Exploring Harmonization Challenges Between Islamic and Positive Law on Polygamy in Indonesia - Bukido, Rosdalina; Makka, Misbahul Munir; Tumiwa, Anisa Jihan; Kolopita, Abdul Fajri (Institut Agama Islam Negeri Kendari, 2024)
The harmonization between Islamic law and positive law regarding polygamy in Indonesia presents significant legal and social challenges. This study aims to explore the complex interactions and conflicts between these legal systems using a structuralist epistemological approach. The research is conducted through an in-depth literature review that analyzes the intersections of Islamic doctrines and civil regulations, specifically focusing on how these structures influence the interpretation and implementation of polygamy-related laws. Findings reveal that while Islamic law allows polygamy under strict conditions, positive law imposes additional constraints to ensure fairness and protect the rights of all individuals involved. The study underscores a significant gap between the legal provisions and their practical enforcement, often influenced by cultural perceptions and social norms. Conclusively, the research suggests that achieving harmonization requires not only legal reforms but also cultural and educational efforts to address the disparities in polygamy's practice and regulation, aiming to uphold both religious traditions and human rights standards. The outcome emphasizes the necessity for a nuanced approach that considers both legal frameworks and the socio-cultural context of Indonesia